2018
DOI: 10.3389/fpls.2018.01191
|View full text |Cite
|
Sign up to set email alerts
|

The Selenium Supplementation Influences Olive Tree Production and Oil Stability Against Oxidation and Can Alleviate the Water Deficiency Effects

Abstract: Foliar fertilization with selenium (Se) may well be beneficial in increasing the nutritional and qualitative values of food in Se-deficient regions such as the Mediterranean Basin, and may contribute to an increase in drought resistance in plants. The present study has considered detachment force, flesh firmness, pigmentation, fresh and dry weight, and oil content of olive drupes from Se fertilized olive orchards (Olea europaea L.) under drought stress and well-watered conditions. This study has also evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 52 publications
(69 reference statements)
0
27
0
Order By: Relevance
“…In plants suffering from drought stress or heat stress, Se fertilization may sustain crop yields by alleviating ROSinduced damages via activation of cellular antioxidant systems (D'Amato et al 2018a;Iqbal et al 2015;Jóźwiak and Politycka 2019;Malerba and Cerana 2018;Sajedi et al 2011). Increased activity of antioxidant enzymes and reduced lipid peroxidation have been reported in wheat, maize and cucumber plants grown under water deficit (Nawaz et al 2016;Yao et al 2009) and in wheat plants subjected to heat stress (Iqbal et al 2015;Jóźwiak and Politycka 2019).…”
Section: Selenium Biofortification In the Context Of Global Environmementioning
confidence: 99%
“…In plants suffering from drought stress or heat stress, Se fertilization may sustain crop yields by alleviating ROSinduced damages via activation of cellular antioxidant systems (D'Amato et al 2018a;Iqbal et al 2015;Jóźwiak and Politycka 2019;Malerba and Cerana 2018;Sajedi et al 2011). Increased activity of antioxidant enzymes and reduced lipid peroxidation have been reported in wheat, maize and cucumber plants grown under water deficit (Nawaz et al 2016;Yao et al 2009) and in wheat plants subjected to heat stress (Iqbal et al 2015;Jóźwiak and Politycka 2019).…”
Section: Selenium Biofortification In the Context Of Global Environmementioning
confidence: 99%
“…Se concentrations were determined via ICP-MS (Agilent 7900, Agilent Technologies, Santa Clara, CA, USA) and an Octopole Reaction System (ORS) following the analytical method of D'Amato et al [20], while the total Ca, Mg, Fe, Cu, and Zn contents were determined using a Shimadzu AA-6200 atomic absorption spectrophotometer (Shimadzu, Tokyo, Japan), as described by Mattioli et al [18].…”
Section: Mineral Evaluation Of Diets and Rabbit Plasmamentioning
confidence: 99%
“…Similarly, Aouidi et al [19] added olive leaf powder to beef meat, thereby inhibiting lipid and protein oxidation and also improving the technological quality of the meat. Proietti et al [20] showed that the dietary intake of Se in sheep can largely offset the effects of oxidative stress on Ca 2+ homeostasis. As a consequence, some animal-originated products, e.g., meat, milk, and eggs, enriched with selenium have been developed and are currently marketed all over the world [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oil and water content of the olives was determined, after fruits crashing, using the "SpectraAlyzer ZEUTEC"-NIR: Near Infra-Red". Each year, one day after harvesting (beginning of November), oil was extracted from two samples of about 2.5 kg per treatment using an artisanal mini olive-mill [23,24]. The determination of the oil chemical characteristics (acidity, peroxide number, total phenol content and fatty acid composition) and the sensory evaluation (panel test) were carried out on 3 subsamples for each oil sample following the Official Methods of Analysis [25].…”
Section: Fruits Production Maturation Indexes and Oil Characteristicsmentioning
confidence: 99%